Determinants and Potential of Trade Using the Gravity Model Approach: Empirical Evidence of Egyptian Rice Crop - Moustafa Ismaiel Ali Ismaiel; Deyi Zhou; Roshdy Shawky Eladawy; Ahmed Abou El-Yazid A. El-Rasoul; Tarek Tawfik Yousef Alkhateeb; Tarek Ali Ahmed Abdullah; Haider Mahmood (Complexity, 2023)
The aim of this study is to examine the determinants of Egyptian trade in general and Egyptian rice trade in particular with 11 rice-importing partner countries (Libya, Lebanon, Syria, Saudi Arabia, Sudan, Jordan, Turkey, the United Kingdom, Ukraine, Belgium, and Romania). To reach the main goals of the study, the gravity model was used to figure out which factors had the most impact on Egypt’s exports and imports. Using annual data on Egypt’s foreign and agricultural trade during the period 2001–2020 and data on the period 2001–2016 of rice crops with the 11 trading partners, the study reached several important conclusions. Among these conclusions, the Egyptian GDP variable had a negative effect on the total value of Egyptian imports and agriculture by increasing the value of total exports, agricultural exports, and rice exports to Egypt. Egyptian imports, exports, and population growth were all hurt by the Egyptian population variable. The study also shows that a 1% increase in export prices leads to a 3.97% increase in shipments of Egyptian rice to partner countries. According to economic theory, higher transportation expenses reduce trade volumes for both exports and imports. The variable distance between capitals has a negative effect on Egyptian exports. The study was designed based on the results of the main investigation. Based on the main investigation, the study made several important recommendations, including the need to take several measures to deflect the pace of economic growth of both the Egyptian total and agricultural export variables and rice export value, focusing on countries with high monetary and real GDP and a close geographical distribution. Improve economic relations between Egypt and its trading partners and shift from import-export cooperation to strategic food security cooperation.